An Avalanche confinement TEPC as connecting bridge from micro to nanodosimetry. (October 2020) - Mazzucconi, D.; Bortot, D.; Pola, A.; Agosteo, S.; Selva, A.; Colautti, P.; Conte, V.
Abstract: It is recognized today that the observable radiobiological effects of ionizing radiations are strongly correlated to the clustering of damages in micrometer- and nanometer-sized subcellular structures, hence to the particle track structure. The characteristic properties of track structure are directly measurable nowadays with bulky experimental apparatuses, which cannot be easily operated in a clinical environment. It is therefore interesting to investigate the feasibility of new portable detectors able to characterize the real therapeutic beams. With this in mind, a novel avalanche-confinement Tissue Equivalent Proportional Counter (TEPC) was constructed for simulating nanometric sites down to 25 nm. Experimental cluster size distributions measured with this TEPC were compared with Monte Carlo simulations of the same experiment and with cluster size distributions measured with the Startrack nanodosimeter.